Association Between Cholangiocarcinoma and Proton Pump Inhibitors Use: A Nested Case-Control Study - Peng, Yen-Chun; Lin, Cheng-Li; Hsu, Wan-Yun; Chow, Wai-Keung; Lee, Show-Wu; Yeh, Hong-Zen; Chen, Chia-Chang; Kao, Chia-Hung (Frontiers in Pharmacology, 2018)
Background: The present study aimed to examine the odds of cholangiocarcinoma (CCA) in patients with proton pump inhibitors (PPIs) use. Methods: A nested case-control study design was employed using data obtained from Taiwan’s National Health Insurance Research Database. In total, 2293 patients with confirmed diagnosis of CCA were identified and served as the CCA group. The CCA patients were propensity score-matched with 2293 subjects without CCA who served as the control group. The cumulative defined daily dose (DDD) of PPIs was calculated based on the total supply in days and quantity of individual PPIs. Univariable and multivariate logistic regression models were used to determine the odds of CCA, and calculated odds ratios (ORs) and 95% confidence intervals (CI) were used to assess PPIs use and odds of CCA. Results: The overall adjusted OR of PPIs use-associated CCA was 2.58 (95% CI 2.27, 2.93). The adjusted OR of CCA by cumulative DDD dose of PPIs and CCA was analyzed and revealed those odds of CCA are associated with all types of PPIs. Conclusions: There were odds of intrahepatic and extrahepatic CCA among PPIs users. All PPIs use was associated with odds of CCA. Analyses of larger numbers of cases are needed to confirm these findings.